Reckoning the ground water recharge in semi-arid region: an assessment of community led policy performance in Saurashtra - Patel, Praharsh; Saha, D. (2019)
Easy access, round the year availability even in the draught years and lack of regulations coupled with advanced and cheap technology to create extraction structure have been major factors responsible for indiscriminate extraction of groundwater. With a rise in population leading to increasing water requirement, the untapped groundwater resource has been the biggest bone of contention amongst multiple stakeholders with a threat of serious depletion in many parts of the world especially regions without perennial surface water availability and arid or semi-arid climate. India is the largest extractor of groundwater and the alarming situation has already tapped in. Semi-arid region of Saurashtra has the most extreme case with just 500 mm of rainfall and almost 40 percent of coefficient of variation leading to frequent drought-like condition. Saurashtra's almost 83 per cent of the total irrigated area is through groundwater. High extraction of groundwater of Saurashtra caused major groundwater depletion in the region. The condition even intensified during consecutive drought years of 1985-87 when Saurashtra received just 93 mm of total rainfall during 1987 on top of 60 per cent rainfall in 2 consecutive drought years of 1985 (299 mm) and 1986 (298 mm). Severity of the condition led to a mass movement for rainwater harvesting as well as a decentralized groundwater recharge at an unprecedented scale. The community-led movement with the support of local leaders, merchants and religious gurus in the early 90s got support from the state government. The movement was formalized as Sardar Patel Sahkari Jal Sanchay Yojana (SPSJSY) soon after Narendra Modi assumed office as Chief Minister of Gujarat. Under this pan-Gujarat scheme, 5 lakh structures created (113738 check dams, 55917 bori bandhs, 240199 farm ponds, besides 62532 large and small check dams) making way for 808 MCM (Million Cubic Meter) of storage capacity. The scheme performed best in Saurashtra as almost 60 per cent of this storage capacity (482 MCM) confined in 7 districts of Saurashtra. The success of the program was much lauded by state and central governments making it exemplary for other semiarid regions like Marathawada and Vidarbha those that have comparable terrain, soil and aquifer characteristics. The comparative analysis of the movement's success with pre-post analysis by considering monsoonal groundwater recharge during good rainfall spell of 1975-84 (pre) and 2004-09 (post) show almost a two-fold increase in the groundwater recharge during the similar monsoon years in Saurashtra. This temporal analysis enables to establish the impact of the collective efforts by people as well as the government for groundwater rejuvenation in Saurashtra. With availability of dependable irrigation, Saurashtra has also emerged as a major contributor to Gujarat state's agriculture growth which has normally been shadowed by other regions of the state making the state agriculture growth reaching the double-digit figure.